Inland dissolved salt chemistry: statistical evaluation of bivariate and ternary diagram models for surface and subsurface waters - Stephen T. THRELKELD; Robert M. BACA (Journal of Limnology, 2000)
We compared the use of ternary and bivariate diagrams to distinguish the effects of atmospheric precipitation, rock weathering, and evaporation on inland surface and subsurface water chemistry. The three processes could not be statistically differentiated using bivariate models even if large water bodies were evaluated separate from small water bodies. Atmospheric precipitation effects were identified using ternary diagrams in water with total dissolved salts (TDS) <25 mg l-1 dominated by SO4 -2, Ca+2, and (Na+ + K+), though water whose inorganic chemistry was dominated by atmospheric precipitation were few. Waters affected by weathering had TDS of 15 to 1,000 mg l-1 and were dominated by (HCO3 - + CO3 -2) and Ca+2. The effects of rock weathering on ion chemistry were the dominant mechanism influencing water chemistry. The contribution of silicates, carbonates, and evaporites to ions in weathering were distinguished using ternary diagrams. Weathering of silicates was evident in low TDS waters, while weathering of carbonates and evaporites was evident in moderate and high TDS waters, respectively. Evaporation effects were first obvious in water around 1,000 mg l-1 TDS as a shift towards higher SO4 -2, Cl-, and (Na+ + K+). At higher TDS, Cl- became the dominant anion while (Na+ + K+) remained the dominant cation. The general patterns were consistent in lakes, rivers, and subsurface water bodies, although subsurface waters did not show an influence due to ions from atmospheric precipitation. While several of the TDS size classes separated statistically into distinct groups, there was wide variation in the pattern of inorganic ions within a TDS size class, especially when TDS >1000 mg l-1. A principal components analysis showed that the variability in the relative proportions of the major ions was related to atmospheric precipitation, weathering, and evaporation. About half of the variation in the distribution of inorganic ions was related to rock weathering. By considering most of the important inorganic ions, ternary diagrams are able to distinguish the contributions of atmospheric precipitation, rock weathering, and evaporation to inland water chemistry.